Effect of different accellerators and inoculums used in fermentation on quality of dead chicken silage flour as feed ingredient for catfish - Bakrie, B.; Sastro, Y.; Sudolar, N. R. (Diponegoro University, 2017)
This research aimed at investigating the effect using molasses and cornmeal as additives with Lactobacillus sp. and Streptomyces sp. as inoculums during fermentation on the quality of silage flour made from dead chickens. The study was conducted using a completely randomized factorial design, consisting of 2 factors with 5 replications. The materials used were the newly dead chickens which were chopped and mixed thoroughly with all ingredients; then transferred into a 5 liters plastic box for fermentation. Observations were made after 3 weeks fermentation, including: a) physical characteristics, b) microbial contents, and c) nutritional contents. The data were calculated using variance analysis utilizing computer program of SPSS version 21.0. It was found that based on the protein contents the Lactobacillus sp. (19.0%) was better than the Streptomyces sp. (17.8%) if combined with molasses and corn meal as the accelerators. However, the fat contents produced were relatively similar for both of the inoculums (mean of 37.8%). It can be concluded that in order to obtain a best fermented product in terms of the protein and fat content, the dead chicken should be fermented using molasses and cornmeal as the accelerator and Lactobacillus sp. as the inoculum.